Local People Perception on Biodiversity Change In Lower Mustang - Paudel, Sambhu; Rayamajhi, Trishna (The Initiation, 2014)
Local people response was obtained on biodiversity change in lower Mustang relying on social survey and from various data sources for natural assets. The main focus was centralized on the change in avifaunal and mammalian diversity and the effect of environmental change on agricultural/livestock forest as well as on grazing land. The change was detected on wildlife movement, livestock depredation, forest stock, palatable species and birds. Climate change is the key issue in conserving biodiversity and linking its goal in livelihood. Change in livelihood pattern seems more adverse factor for community development as urbanization is prevalent. Animals and birds solely dependent in the nutshell area are at increasing rate but transition (forest and agriculture) species are decreasing. DOI: http://dx.doi.org/10.3126/init.v5i0.10256 The Initiation 2013 Vol.5; 68-74